Analysis of the Factors Affecting the Migration of Labor from the Agricultural Sector to the Industrial Sector (Case Study in Kerek District, Tuban Regency) - Ahmad Husnun Niam (TRIGIN PUBLISHER, 2020)
The movement of labor from the agricultural sector to the industrial sector also affects the workforce in rural areas as a whole. The pattern of labor absorption in rural areas is an illustration of the pattern of labor absorption in Indonesia. This is because most of Indonesia's population lives in rural areas. This study aims to determine 1). Variables that affect the movement of labor from the agricultural sector to the industrial sector 2). Knowing the dominant variables that affect the movement of labor from the agricultural sector to industry. From the results of the study, it was found that the education factor, the wage level factor and the land area factor are factors that influence the movement of workers from the agricultural sector to the industrial sector and the most dominant factor influencing the movement of workers is the level of education where the higher the level of education of farmers, the higher the level of education of farmers. the opportunity to move to the industrial sector is getting bigger, and their desire to leave agriculture is getting higher because many have skills other than farming experience. Although the growth of the agricultural sector has always decreased, We cannot ignore this development in the agricultural sector because most parts of Indonesia are rural and it is necessary to improve the labor arrangement so that there is no shortage of workers working in the agricultural sector. This is not only a characteristic of our country, where the majority of the population lives in rural areas, but is also caused by the growing unemployment problem and needs to find a solution.